W oczekiwaniu na bunt młodych = In anticipation of the youth rebellion - Szafraniec, Krystyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the article, the author deals with the issue of the youth rebellion, which is both the scientific and media problem. The author believes that the issue of the youth rebellion is still an intriguing phenomenon and it is worth dealing with. The imperative of tracking the potential of the rebellion among the youth results from the sociological thesis according to which the situation and rebellious behaviour of the young always signalize critical and crisis states in a society, provide an early warning mechanism, reveal (but also relieve) tensions of a system.
Keywords: youth; generation gap; youth rebellion; młodzież; przepaść pokoleniowa; bunt młodzieży